Perception of BDS students of Kathmandu University on online learning during COVID-19 pandemic - Gupta, Alka; Shrestha, Rabindra Man; Shrestha, Sujita; Acharya, Asal; Pandey, Nashib (Orthodontic Journal of Nepal, 2020)
Introduction: The spread of COVID-19 pandemic has gripped the entire world and caused widespread public health concerns, hampered economics and education system immensely. Online classes have been an alternative to give continuity to the theory classes. The objective of this study is to assess the various aspects of online classes and perception of Bachelor of Dental Surgery (BDS) students of Kathmandu University (KU) during COVID-19 pandemic. Materials and Method: Cross-sectional, questionnaire based descriptive study using online Google form was distributed among the BDS students of KU. The questionnaire was distributed via social media. Frequency distribution of the descriptive data was done. Chi-square test was done to assess the difference in perception about online classes between the basic science and clinical science students. Result: 89% of the students had never attended any online classes before online education due to COVID-19 pandemic. 76.9% agreed that the online class is distracting. 57.5% used smartphone for seeking online class and medium most frequently used was Zoom platform. 70.2% students could ask questions, communicate & receive response during online class. 55.4% students disagreed that online classes are more effective. Statistical significant differences were seen in students submitting assignments, communication and practical simulation among basic science and clinical science students. Conclusion: Online class can serve as an alternative effective educational tool. With more practice, system upgrading, capacity building of the student-teacher; it is bound to be more effective as well as efficient. The online class should be designed in such a way that student can focus and find it more interesting and should introduce various strategies to increase the interaction between students and teachers. Further, training on online class is required for both course recipients and providers.